2004
DOI: 10.1002/humu.20040
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional analysis ofSUMF1 mutations in multiple sulfatase deficiency

Abstract: Multiple sulfatase deficiency (MSD) is a rare disorder characterized by impaired activity of all known sulfatases. The gene mutated in this disease is SUMF1, which encodes a protein involved in a post-translational modification at the catalytic site of all sulfatases that is necessary for their function. SUMF1 strongly enhances the activity of sulfatases when coexpressed with sulfatase in Cos-7 cells. We performed a mutational analysis of SUMF1 in 20 MSD patients of different ethnic origin. The clinical presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
84
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 22 publications
2
84
0
3
Order By: Relevance
“…Analysis of the SUMF1 mutations in MSD revealed multiple types including missense, nonsense, deletions and splice mutations 32 . The effect of these mutations on enzyme activity is variable as is the clinical picture in MSD patients; however, a lack of genotype-phenotype correlation indicates the existence of additional causative factors, either genetic or non-genetic, which could contribute to disease pathogenesis 32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the SUMF1 mutations in MSD revealed multiple types including missense, nonsense, deletions and splice mutations 32 . The effect of these mutations on enzyme activity is variable as is the clinical picture in MSD patients; however, a lack of genotype-phenotype correlation indicates the existence of additional causative factors, either genetic or non-genetic, which could contribute to disease pathogenesis 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of these mutations on enzyme activity is variable as is the clinical picture in MSD patients; however, a lack of genotype-phenotype correlation indicates the existence of additional causative factors, either genetic or non-genetic, which could contribute to disease pathogenesis 32 . This leads to the speculation that miR-95, via its regulation of SUMF1, and perhaps also additional targets related to lysosomal function, could contribute to the pathogenesis MSD or other LSDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Until now, more than 30 different SUMF1 mutations were found, most of which are missense mutations. 9,23,26,20,27 In a first approach, we investigated the consequences of four different MSD causing SUMF1 mutations on FGE 13 expression, localization, stability and activity in either an overexpressing cell-culture model or in patient fibroblasts. We found that all four variant FGE proteins could be expressed in HT-1080 cells, correctly localizing to the ER.…”
Section: Introductionmentioning
confidence: 99%
“…So far, 30 mutations in SUMF1 have been described in MSD patients including nine nonsense and 21 missense mutations [Dierks et al, 2003;Cosma et al, 2003;Cosma et al, 2004;Dierks et al, 2005;Diaz-Font et al, 2005]. Mature FGE is made up of a 341-amino acid polypeptide, which adopts a single domain monomeric structure with a unique fold .…”
Section: Introductionmentioning
confidence: 99%